Supply chain practices and firms’ operational performance: an empirical study of Vietnam garment industry - Huy Truong (2014)
Purpose: This study aims at providing an empirical evidence about the relationship between practices of supply chain management (SCM) and operational performance. Design/methodology/approach: Based on a comprehensive literature review and the practical experience in the field of the Vietnam garment industry, a set of management practices have been identified and selected to develop a conceptual model as well as to establish their relationship to companies’ operational performance. Structural equation modelling (SEM) was used to evaluate the validity of the model. The measurement instrument of practices was developed in 4 steps: (1) identification and development of initial instrument, (2) personal interviews and Q-sort, (3) large-scale data collection and (4) large-scale analysis in order to ensure unidimensionality, reliability and validity. Data were collected in Vietnamese garment enterprises. Findings: The study showed that the four practices: customer focus, supplier management, process control and improvement, top management support are positively related to operational performance. In addition, this study also showed that these SCM practices could explain 52.6% variance of operational performance. Research limitations/implications: There were some limitations that can guide academics to new lines of further research: (i) to extend the scope of the survey to include different countries and new situations, so results can be generalized and (ii) to explore additional factors that can further explain operational performance, such as operational environment, capital, technology, human resource, etc.Practical implications: Research results gave some suggestions for business associations and government in order to issue the specific and practical policies creating good conditions for enterprises to get higher performance. Originality/value: The proposed research model analyzing the relationship among SCM practices and operational performance and its validation using the Vietnam garment industry provided valuable insights both from theoretical and practical perspectives. The results of this study, moreover, help to understand the weaknesses of this industry. SEM, which was used in this study to test the measurement instrument and structural model, is one of modern and complex data analysis methods and can provide higher accuracy in the quantitative research.